Emerging Antimicrobial Resistance Patterns in Pediatric Urinary Tract Infections: A Tertiary Care Perspective - Venugopal, Aishwarya; Krishnan, Anjana S R; Bhat Y, Ramesh; H O, Niranjan Kumbara (Indian Journal of Child Health, 2025)
Background: Urinary tract infections (UTIs) are a common pediatric concern that can lead to significant morbidity if improperly managed. The objective of this study is to determine the etiological profile and antimicrobial resistance patterns of uropathogens in children aged 1 month to 5 years. Methodology: A prospective observational study was conducted in a tertiary care government medical college involving 96 children between 1 month to 5 years of age presenting with UTI. Aetiology was confirmed using standard microbiological methods, and antimicrobial susceptibility testing was conducted [1]. Results: Of the 96 children, 50 showed significant bacterial growth. Escherichia coli (66%) and Klebsiella pneumoniae (18%) were the predominant pathogens. Multi-drug resistance was observed in 75% of E. coli and 66% of Klebsiella isolates. Sensitivity remained high for Amikacin and Imipenem. Conclusion: The high prevalence of multidrug-resistant uropathogens underscores the importance of antibiotic stewardship and region-specific antibiogram-based empirical therapy in children [2, 3].